Next-Gen Transformation of Insurance Document Management - Sanath Chilakala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Artificial Intelligence in the insurance industry’s document and letter generation processes marks a transformative advancement in operational efficiency. This technical article examines the comprehensive implementation of AI technologies across various aspects of insurance documentation, including policy generation, claims processing, and customer correspondence. The article analyzes the architectural framework, focusing on Natural Language Processing and Machine Learning components that form the backbone of modern insurance systems. The article demonstrates how AI-driven solutions have revolutionized traditional document processing workflows by thoroughly examining implementation strategies, key applications, and technical benefits. The article also explores advanced features and future developments, highlighting the potential for quantum computing, blockchain integration, and enhanced personalization capabilities in next-generation insurance systems.